Grace and Frankie. Season 2 [videorecording (DVD)] - Fonda, Jane, 1937-; Tomlin, Lily; Sheen, Martin; Waterston, Sam
After learning their ex-husbands plan to marry one another, lifelong rivals Grace and Frankie have bonded in an uneasy friendship. The second season of this acclaimed comedy series brings more laughs and surprises as Grace and Frankie tackle the challenges of family and relationships, while driving each other crazy on a regular basis.